2020
DOI: 10.1186/s12887-020-1967-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations between motor proficiency and academic performance in mathematics and reading in year 1 school children: a cross-sectional study

Abstract: Background: A key priority for learning during the early years of school is for children to develop skills in numeracy and literacy. Consequently, less time may be allocated in the curriculum to foster other important developmental areas, including the ongoing motor skill development of school children, which has been positively linked to academic performance. In order to promote holistic approaches to teaching and learning in the early years of school, it is necessary to further delineate the nature of associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 29 publications
(49 reference statements)
2
14
0
3
Order By: Relevance
“…Our results are also coherent with other studies in that specific fine motor skills have been found to be more closely linked to academic competencies than specific gross motor skills (Grissmer et al, 2010;Pagani et al, 2010;Pagani and Messier, 2012;Gandhi et al, 2013;Cameron et al, 2016;Pitchford et al, 2016;Zhang et al, 2019). In fact, in our study, specific gross motor skills were not found to be associated with academic competencies, also in accordance with the results of other authors (Grissmer et al, 2010;Pagani et al, 2010;Pagani and Messier, 2012;Gandhi et al, 2013;Pitchford et al, 2016;Macdonald et al, 2020). However, in the literature, certain results contradict this finding: some authors suggest significant associations between gross motor skills and academic competencies both in the literacy and mathematical domains (Son and Meisels, 2006;Pagani et al, 2010;Abdelkarim et al, 2017;de Waal, 2019).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are also coherent with other studies in that specific fine motor skills have been found to be more closely linked to academic competencies than specific gross motor skills (Grissmer et al, 2010;Pagani et al, 2010;Pagani and Messier, 2012;Gandhi et al, 2013;Cameron et al, 2016;Pitchford et al, 2016;Zhang et al, 2019). In fact, in our study, specific gross motor skills were not found to be associated with academic competencies, also in accordance with the results of other authors (Grissmer et al, 2010;Pagani et al, 2010;Pagani and Messier, 2012;Gandhi et al, 2013;Pitchford et al, 2016;Macdonald et al, 2020). However, in the literature, certain results contradict this finding: some authors suggest significant associations between gross motor skills and academic competencies both in the literacy and mathematical domains (Son and Meisels, 2006;Pagani et al, 2010;Abdelkarim et al, 2017;de Waal, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…They found that Coordination was only associated with mathematical aspects, but not with literacy. As for Integration, our results, like those of the literature, revealed associations with both literacy and mathematics competencies (Grissmer et al, 2010;Dinehart and Manfra, 2013;Manfra et al, 2016;Pitchford et al, 2016;Duran et al, 2018;Macdonald et al, 2020).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In Kindergarten students, the form of physical activity that contains perceptual motor elements and is packaged in the form of play is very important. This is based on the findings of several research results, including: (1) there is a relationship between academic ability and perceptual motor skills, (Nourbakhsh, 2006); (2) the ability of spelling, reading, and mathematics of children aged 4-6 years is influenced by perceptual motor in terms of kinesthetic, visual, and auditory, (Dhingra et al, 2010); (3) cognitive skills of preschool children are influenced by physical activity programmed in a certain period, (Hosseini et al, 2011); (4) academic achievement is influenced by perceptual motor skills, children have good cognitive if supported by good perceptual motor skills, (Morales et al, 2011); (5) motor skills have a relationship with academic performance, in mathematics for grade 1 elementary school children, (Macdonald et al, 2020); (6) Perceptual motor has a relationship with basic motor skills in children aged 5-7 years, (Hyungmin & Johan, 2012); (7) the perceptual motor program intervention in children aged 6-7 years is effective in improving gross and fine motor skills as well as reading and spelling abilities., (Botha & Africa, 2020); (8) the perceptual motor exercise program can develop agility, running, balance, coordination and strength abilities in children aged 8-11 years who experience High Function Autistic Disorder., (Azar & Akbar, 2018); (9) the perceptual motor program given to Kindergarten children aged 4-6 years can improve gross and fine motor skills, (Sajedi & Barati, 2014); (10)perceptual motor development can be developed optimally in children aged 3-6 years, (Johnstone & Ramon., 2011); (11)the involvement of perceptual motor elements in the task of motion, through a form of play, really needs to be done by the teacher, in order to attract and make students happy, (Ningrum & Sukoco, 2017); and (12) Perceptual Motor Training (PMT) has an influence on gross motor development of children aged 5-6 years. Motor improvement rough child can be seen from the child who is able to do a variety kinds of locomotor motion, manipulative motion, and balance with correct and directed, (Lukmawati et al, 2019).…”
Section: Preliminarymentioning
confidence: 99%
“…A growing literature suggests that academic achievement can be selectively associated with motor proficiency in pupils attending primary school. For instance, Macdonald et al. (2020) documented that during the first year of primary school, fine motor integration skills predict the performance of mathematic skills, for example, numerical operations and math reasoning, and reading skills, for example, decoding words and pseudowords.…”
Section: Motor Proficiency and Academic Achievement In Pupils With Anmentioning
confidence: 99%